2015
DOI: 10.7448/ias.18.1.19962
|View full text |Cite
|
Sign up to set email alerts
|

Perception of sexuality and fertility in women living with HIV: a questionnaire study from two Nordic countries

Abstract: IntroductionAs the human immunodeficiency virus (HIV)-positive population ages, issues concerning sexuality and fertility, among others, are becoming relevant. HIV is still surrounded by stigma and taboos, and there have been few studies conducted in industrialized settings concerning these questions. We therefore wanted to investigate the perception of sexuality and fertility in women living with HIV (WLWH) in an industrialized setting, using a questionnaire.MethodsWLWH were recruited at their regular outpati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 25 publications
2
20
0
1
Order By: Relevance
“…This qualitative study adds knowledge to the Hernando et al [ 4 ] previous study, which showed desire for procreation in HIV-positive women in Spain was prevalent, as was also demonstrated by research performed in other European countries [ 3 , 19 ]. Our study allows for an in depth understanding of barriers and drivers for procreation in HIV positive women, and impact of HIV infection on them.…”
Section: Discussionsupporting
confidence: 76%
“…This qualitative study adds knowledge to the Hernando et al [ 4 ] previous study, which showed desire for procreation in HIV-positive women in Spain was prevalent, as was also demonstrated by research performed in other European countries [ 3 , 19 ]. Our study allows for an in depth understanding of barriers and drivers for procreation in HIV positive women, and impact of HIV infection on them.…”
Section: Discussionsupporting
confidence: 76%
“…This is significant because even though this review has aimed to account for the effects of cultural differences between high‐ and low‐income countries, the fact that the majority of the participants in the majority of the studies, excluding Wessman et al . (), were either African American or immigrants from lower income countries, may in fact mean that cultural differences between the participants have not been accounted for. Whilst it is important to understand that in a modern secular society, cultural diversity is the norm, it must also be considered that large populations of immigrants often form subcultures within their new countries that promote different values and health beliefs from those of the dominant culture (Andrews et al .…”
Section: Discussionmentioning
confidence: 99%
“…Women with HIV therefore face unique challenges, such as in partner relationships, sexual satisfaction and childbearing (Bharat & Mahendra, 2007; Carter et al, 2013; Florence et al, 2004). Many women living with HIV have a desire to give birth to a child (Carter et al, 2017b; Wessman et al, 2015), a desire which can further increase feelings of stigmatization, shame and fear (Sandelowski & Barroso, 2003; Sanders, 2008). In a meta-synthesis of 18 qualitative studies, it was demonstrated that HIV was a burden in relation to sexuality and reproduction for HIV-positive women, and that the burden comprises fear of transmitting HIV to a partner or infant (Carlsson-Lalloo, Rusner, Mellgren, & Berg, 2016).…”
Section: Introductionmentioning
confidence: 99%